Parents Acceptance To Visual Impaired Children In Special Chool At Singkawang - Basith, Abd; Hengky, Hengky (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2017)
The purpose of this research are: (1) describe and analyze the description of acceptance of parents of blind children at Special School Singkawang, (2) identify the factors acceptance of parents of blind children at Special School Singkawang. This study used qualitative methods, techniques interview data collectors tested its validity through triangulation. Subjects in this study are the parents of students with visual impairment in Special School Singkawang many as four people and classroom teachers as informants two people. Data analysis techniques in the form of data reduction, data display and conclusion. The results showed that:Â (1) The parents of blind children can receive willingly conditions experiencedÂ by his son, even that happens on stage tertiary phase which should at that stage parents could not accept her son. However, with sincerity and greatsincerity and love to their children so that the parents that their children canreceive in a faster time. (2) There are several factors acceptance of parents of blind children is the support of family, lingungan very accepting andÂ relatives who frequently give feedback, even one of the parents said that children with special needs is preferable compared with a normal.